A prospective comparative study of internal fixation of diaphyseal forearm fractures with LCP and DCP in above 50 year age group - Reddy, P. Amarnath; Dinesh Reddy, C. (International Journal of Research in Orthopaedics, 2018)
Background: In orthopedic practice forearm bone fracture is commonly encountered fracture. Forearm plays a vital role in day to day activities without which a person is unable to perform his role in his own life. It has been estimated that around 31% of the total fractures of the upper limb are of forearm fractures. The objective of the study was to study and compare internal fixation of diaphyseal forearm fractures with LCP and DCP in above 50 year age group Methods: Present study was hospital based study. This was a prospective study. A total of 50 patients with fracture of both bones in the forearm were included in the present study. They were divided randomly as 25 patients in each group. They were followed for about eight months. Results: Both the groups in the present study were found to be comparable in terms of age, sex, mode of injury, type of injury and level of fracture. It took only 13.83 weeks for radiological union in LCP group and it took a longer in DCP group of 15.33 weeks. This difference was found to be statistically significant. Overall functional results were almost same in both the groups. Excellent in 36 cases (19 in LCP, 17 in DCP), Good in 10 cases (4 in LCP, 6 in DCP), fair in 4 cases (2 in each group). Conclusions: It has been concluded from the present study that union of fracture after LCP had taken significantly lesser time as compared to the DCP technique. Hence especially in persons above 50 years, LCP should be used.